The underground church : nonviolent resistance to the Vatican empire - Kautzer, Kathleen (Leiden ; Boston : Brill, 2012)
Drawing on theories of religious movements and nonviolent resistance strategies, this book analyzes the Reform Movement of liberal American Catholics who for over four decades have sustained a movement to expand on the reforms and visions of Vatican II. In the face of backlash from church officials, reformers have moved in a sectarian direction.
pt. 1. Burned out, bummed out, and thrown out : progressive reformers begin their wilderness journey -- pt. 2. Testing the waters and pushing the boundaries -- pt. 3. Notes from the underground.
Includes bibliographical references and index.
Master record variable field(s) change: 611
Keywords: Voice of the Faithful (Organization); Catholic Church -- History -- 21st century; Voice of the Faithful (Organization); Catholic Church; Church renewal -- Catholic Church; Laity -- United States -- History -- 21st century; Laity -- Catholic Church -- History -- 21st century; Liberalism (Religion) -- Catholic Church; RELIGION -- Christianity -- Catholic; Electronic books